2021
DOI: 10.3390/app11020515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Nitriding on Surface Characteristics and Wear Resistance of NiTi Alloy with Low Power Fiber Laser

Abstract: The laser nitriding was performed in nitrogen gas at room temperature (20 °C) and low temperature (−190 °C) by a low power fiber laser to modify the wear and abrasion resistance of NiTi alloy. The surface roughness and element composition were analyzed by roughness device and energy-dispersive X-ray spectroscopy respectively. The results of roughness show that laser treatment can change the surface roughness due to the laser remelting. The effect of laser nitriding on the microhardness, friction coefficient, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The papers of [160,161] indicated that laser treatment in a nitrogen environment caused the formation of TiN, which significantly improved the surface hardness and wear resistance of the materials. The increased wear resistance was explained by a decrease in the coefficient of friction [160]. The research of [161] indicated that the relative wear resistance increased by 1.7 times compared to a material without a laser treatment.…”
Section: Wear Resistance and Fatigue Behaviormentioning
confidence: 99%
“…The papers of [160,161] indicated that laser treatment in a nitrogen environment caused the formation of TiN, which significantly improved the surface hardness and wear resistance of the materials. The increased wear resistance was explained by a decrease in the coefficient of friction [160]. The research of [161] indicated that the relative wear resistance increased by 1.7 times compared to a material without a laser treatment.…”
Section: Wear Resistance and Fatigue Behaviormentioning
confidence: 99%